2018
DOI: 10.1371/journal.pone.0203409
|View full text |Cite
|
Sign up to set email alerts
|

Local release of tacrolimus from hydrogel-based drug delivery system is controlled by inflammatory enzymes in vivo and can be monitored non-invasively using in vivo imaging

Abstract: BackgroundLocal drug delivery systems that adjust the release of immunosuppressive drug in response to the nature and intensity of inflammation represent a promising approach to reduce systemic immunosuppression and its side effects in allotransplantation. Here we aimed to demonstrate that release of tacrolimus from triglycerol monostearate hydrogel is inflammation-dependent in vivo. We further report that by loading the hydrogel with a near-infrared dye, it is possible to monitor drug release non-invasively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Moreover, systemic concentrations reached subtherapeutic levels one week after injection and were measurable until POD58 whereas tissue levels were measurable until POD100, demonstrating a lower systemic drug exposure and higher tissue concentrations than FK506 disks 9 . We recently reported the formation of a capsule around injected tacrolimus-loaded hydrogel 26 and the same is reported for other ISFI and biomaterials 27 . It is likely that also Rapa-ISFI are encapsulated after injection.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, systemic concentrations reached subtherapeutic levels one week after injection and were measurable until POD58 whereas tissue levels were measurable until POD100, demonstrating a lower systemic drug exposure and higher tissue concentrations than FK506 disks 9 . We recently reported the formation of a capsule around injected tacrolimus-loaded hydrogel 26 and the same is reported for other ISFI and biomaterials 27 . It is likely that also Rapa-ISFI are encapsulated after injection.…”
Section: Discussionsupporting
confidence: 74%
“…It is likely that also Rapa-ISFI are encapsulated after injection. However, we could not retrieve any of the implant in long term surviving rats, suggesting that, similarly to tacrolimus hydrogels 26 , the formation of a fibrous wall did not prevent the interaction of the ISFI with the surrounding tissues. However, the degree of the foreign body reaction triggered by the ISFI injection should be further investigated to support the translation of this approach to patients.…”
Section: Discussionmentioning
confidence: 81%
“…26,27 Also, common immunosuppressive drugs like calcineurin inhibitors, glucocorticoids and anti-TNF-α antibodies have been used to promote the functionality and tissue regeneration around the biomaterials. [28][29][30] For instance, inhibiting inflammation by loading collagen-hydrogels with resveratrol improved bone and cartilage regeneration and repair, 31 suppression of IFN-γ and TNF-α was able to enhance bone regeneration 32 and incorporating resolvin D1 in chitosan 3D sponges showed a general decrease in pro-inflammatory cytokines. 33 Regarding silkbased biomaterials, Kweon and colleagues have reported that 4-hexylresorcinol is able to inhibit FBGC formation in response to silk fibroin.…”
Section: Introductionmentioning
confidence: 99%
“…Cellbased therapies might also improve the immunologic outcomes in VCA [50][51][52]. The use of locally administered immunosuppression bears a huge potential to minimize the side-effects of systemic immunosuppression as well [53][54][55][56][57][58]. Recently, a new desensitization protocol including fludarabine, myeloablative irradiation, and bone marrow transplant showed promise in small animal model of VCA, as sensitized transplant candidates are highly prevalent and are major barriers for a successful VCA transplant [59].…”
Section: Discussionmentioning
confidence: 99%